Quercetin ameliorates ulcerative colitis by restoring the balance of M2/M1 and repairing the intestinal barrier via downregulating cGAS‒STING pathway - Gao, Fei; Zhu, Feng; Shuai, Bo; Wu, Meng; Wei, Chunzhu; Yuan, Yuyi; Gui, Yang; Tian, Yushi; Fan, Heng; Wu, Hui (Frontiers in Pharmacology, 2024)
Macrophage polarization is closely associated with the pathogenesis of ulcerative colitis (UC). Quercetin, a flavonoid, has shown promise as a treatment for inflammatory diseases, but its specific mechanism of action remains unclear. This study investigates whether quercetin can regulate intestinal macrophage polarization and promote intestinal tissue repair via the cGAS-STING pathway for the treatment of UC. In vivo, mice with 3% DSS-induced UC were intraperitoneally injected with quercetin and RU.521 for 7 days, following which their general conditions and 2 corresponding therapeutic effects were assessed. The impact of interferon-stimulated DNA (ISD) and quercetin on macrophage polarization and the cGAS-STING pathway was investigated using RAW264.7 cells and bone marrow-derived macrophages (BMDMs) in vitro. The results demonstrated that ISD induced M1 macrophage polarization and activated the cGAS-STING pathway in vitro, while quercetin reversed ISD's inflammatory effects. In vivo, quercetin suppressed the cGAS-STING pathway in the intestinal macrophages of DSS-induced UC mice, which reduced M1 macrophage polarization, increased M2 polarization, and facilitated intestinal barrier repair in UC. Taken together, these findings provide new insights into the mechanisms via which quercetin could be used to treat UC.